Maize yield improvements in China: past trends and future directions. Issue 2 (15th February 2016) - Qin, Xiaoliang; Feng, Fan; Li, Yajun; Xu, Shutu; Siddique, Kadambot H. M.; Liao, Yuncheng
Abstract: Maize is one of China's most important grain crops. We analysed data from breeding trials and experimental reports to assess genetic gains in the single‐cross varieties in terms of grain yield and agronomic traits in Northern China, Southwestern China and Yellow–Huai River Valley. Since the 1960s, the grain yield of single‐cross varieties has increased linearly in all three regions. Plant height, ear rows and 100‐seed weight have increased linearly (P < 0.05) with time, while ear length has decreased (P < 0.05). Planting density has increased (P < 0.05) in Yellow–Huai River Valley and Northern China, but no change in Southwestern China. Ear height and leaf number in Northern China and Southwestern China have increased linearly (P < 0.05) over time, but no change in Yellow–Huai River Valley. The growing period in Yellow–Huai River Valley has increased linearly (P < 0.05), while that of Northern China and Southwestern China has not changed. Our analysis showed that contribution of agronomic traits to grain yield differed between agroecological regions. Future research and breeding strategies should focus on specific agroecological regions.